2014
DOI: 10.1177/000313481408000416
|View full text |Cite
|
Sign up to set email alerts
|

Margin Status Impacts Survival after Pancreaticoduodenectomy but Negative Margins Should Not be Pursued

Abstract: Negative margins are the goal with pancreaticoduodenectomy for pancreatic adenocarcinoma. Thereby, margins are assessed intraoperatively with frozen section analysis and negative margins are pursued. This study was undertaken to determine the impact of margin status with pancreaticoduodenectomy for pancreatic adenocarcinoma and the value of extending resections to achieve negative margins. The intraoperative frozen section analysis and final margins for 448 patients undergoing pancreaticoduodenectomy for pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 29 publications
1
46
2
2
Order By: Relevance
“…For overall survival, adverse prognostic factors were surgical resection margin status and elevated BUN or bilirubin at baseline. The surgical resection margin is most likely associated with inferior long‐term outcomes, although data are controversial . A possible reason for these discrepant findings is that the surgical resection margin status is an amalgam of various factors, such as patient selection for surgery, surgical volume and technique of pathologic assessment, disease biology, and the effect of any preoperative chemotherapy or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For overall survival, adverse prognostic factors were surgical resection margin status and elevated BUN or bilirubin at baseline. The surgical resection margin is most likely associated with inferior long‐term outcomes, although data are controversial . A possible reason for these discrepant findings is that the surgical resection margin status is an amalgam of various factors, such as patient selection for surgery, surgical volume and technique of pathologic assessment, disease biology, and the effect of any preoperative chemotherapy or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…These patients may not benefit from the current standard of care but to our knowledge little is known regarding how best to identify such patients at high risk of early mortality. Surgical resection margin has been shown to be associated with survival outcomes, although there are some contradictory reports owing to nonstandardized pathologic margin assessment . CA 19‐9 is another marker reported to have varying associations with survival .…”
Section: Introductionmentioning
confidence: 99%
“…28,38,39 Pursuit of negative margins after positive intraoperative frozen-section analysis has been shown to be associated with worse survival than negative margins on initial intraoperative frozen sections. 40,41 In addition, comparability of studies on resection margin status is often plagued by frequent underreporting of microscopic margin involvement due to inconsistent pathologic review practices. 42 Neoadjuvant therapy has also shown to alter the consistency of the pancreas, which may impact pathologic evaluation of tumor cells at the circumferential margin.…”
Section: Discussionmentioning
confidence: 99%
“…109 Microscopically positive margins (R1 resection) are associated with reduced survival in patients with pancreatic ductal adenocarcinoma. [120][121][122][123] The reported rate of R1 resections for locally advanced pancreatic ductal adenocarcinoma following neoadjuvant therapy varies widely from 0 to 51%. [124][125][126] A relatively recent meta-analysis of 111 studies found that of patients who were considered non-resectable prior to neoadjuvant therapy, 33.2% eventually underwent surgical resection with an R0 rate of 79.2%.…”
Section: Handling and Reporting Of Treated Pancreatic Adenocarcinomamentioning
confidence: 99%